Intra-ovarian stem cell transplantation in management of premature ovarian insufficiency: towards the induced Oogonial Stem Cell (iOSC) - Celik, Onder; Ak, Mehmet; Sahin, Erdem; Senturk, Senol; Ugur, Kader; Celik, Sudenaz; Aydin, Suleyman (C M B Assoc, 2020)
The specialized resident-stem cells in gonads are tasked with restorating damaged ovarian cells following injury to maintain sequential reproductive events. When we talk about premature ovarian insufficiency (POI) we accept the existence of decreased stem cell and their regenerative abilities. The present study was to explain how restorating damaged ovarian cells following injury to maintain sequential reproductive events in evidence-based medicine indexed in PubMed and Web of Science. The exact mechanism is unclear stem cells transfer may improve compromised ovarian function and fertility outcome in women with POI. Soluble factors secreted by stem cell may rescue impaired mitochondrial function in oogonial stem cells, enhance metabolic capacity of resident stem cells, induce local neovascularization in the ovary, and activate gene shifting between transferred stem cells and germ cell precursors. This review may provide insight into how stem cells show some of their beneficial effects on compromised ovarian microenvironment and germ cell niche and paves the way for clinical trials for improving ovarian function of women with POI. We also had the opportunity to share our hypothesis about the design and development of induced oogonial stem cell (iOSC) and its use in POI.
Keywords: Oogonial stem cell; Stem cell transplantation; Premature ovarian insufficiency